2016
DOI: 10.1002/mc.22537
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin inhibits hypoxia‐induced HIF‐1α‐mediated signaling, angiogenesis and lipogenesis in prostate cancer cells: In vitro evidence and in vivo functional imaging and metabolomics

Abstract: Hypoxia is associated with aggressive phenotype and poor prognosis in prostate cancer (PCa) patients suggesting that PCa growth and progression could be controlled via targeting hypoxia-induced signaling and biological effects. Here, we analyzed silibinin (a natural flavonoid) efficacy to target cell growth, angiogenesis and metabolic changes in human PCa, LNCaP and 22Rv1 cells under hypoxic condition. Silibinin treatment inhibited the proliferation, clonogenicity and endothelial cells tube formation by hypoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 54 publications
0
42
0
Order By: Relevance
“…High HIF‐1α expression has been shown to be associated with metastasis, resistance to radiotherapy, castration resistance, chemoresistance and biochemical recurrence in patients with PCa . Many HIF‐1α inhibitors have been developed and used to improve treatment success . To date, there are no non‐invasive methods to assess the expression of HIF‐1α in PCa, and no data investigating the relationship between HIF‐1α expression and GS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High HIF‐1α expression has been shown to be associated with metastasis, resistance to radiotherapy, castration resistance, chemoresistance and biochemical recurrence in patients with PCa . Many HIF‐1α inhibitors have been developed and used to improve treatment success . To date, there are no non‐invasive methods to assess the expression of HIF‐1α in PCa, and no data investigating the relationship between HIF‐1α expression and GS.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with these biomarkers, nuclcar‐associated antigen Ki‐67 (Ki‐67), hypoxia‐inducible factor‐1α (HIF‐1α) and vascular endothelial growth factor (VEGF) can reflect the biological activity of certain tumor cells in specific regions. Recently, Ki‐67, HIF‐1α and VEGF have been used as prognostic biomarkers for the prediction of aggressiveness, prognosis and overall survival rate in patients with PCa . Previous studies have shown that Ki‐67 and/or VEGF are associated with the grade of tumor in PCa, astrocytomas and oligodendrogliomas, and osteosarcoma …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an in vivo study, an oral treatment with silibinin in male nude mice with 22Rv1 tumors inhibited tumor vascularity and, thus, tumor growth without directly inducing necrosis. In addition, feeding with silibinin resulted in a reduction of proliferation and angiogenesis and on the levels of HIF‐1α, fatty acid synthase, and acetyl‐Co A carboxylase (Deep et al, ).…”
Section: Silymarin Anticancer Effects: What Has Been Discovered So Far?mentioning
confidence: 99%
“…In some investigations, Silibinin decreases micro-vessel density in prostate carcinoma tumors by decreasing VEGF expression. Others found that Silibinin targeted the onset of angiogenesis in prostate cancer and inhibited signaling originated by HIF-1α (13,14). In terms of colorectal cancers, Silibinin also inhibited angiogenesis through a decrease in expression and production of VEGF, HIF-1α، COX2, and iNOS (15).…”
Section: Introductionmentioning
confidence: 99%